Catheter Ablation of Ventricular Arrhythmias Originating From the Region of DGCV-AIV via a Swartz Sheath Support Approach - Zheng, Cheng; Lin, Wei-Qian; Wang, Yao-Ji; Lv, Fang-Zhou; Jin, Qi-Qi; Li, Jin; Lin, Jia-Feng (Frontiers in Cardiovascular Medicine, 2021)
Abstract AIMS This study aimed to investigate an appropriate catheter manipulation approach for ventricular arrhythmias (VAs) originating from the left ventricular epicardium adjacent to the transitional area from the great cardiac vein to the anterior interventricular vein (DGCV-AIV). METHODS One hundred twenty-three patients with DGCV-AIV VAs were retrospectively analyzed. All these patients underwent routine mapping and ablation by conventional approach （Non-Swartz sheath support (NS) approach）firstly. In the situation of distal portion of coronary venous system （CVS） not accessed or a good target site not obtained , Swartz sheath support (SS) approach was attempted alternatively. If still failed, the hydrophilic coated guidewire and left coronary angiographic catheter-guided deep engagement of Swartz sheath in GCV to support ablation catheter was performed. RESULTS A total of one hundred three VAs (103/123, 83.74%) were successfully eliminated in DGCV-AIV. By NS approach, the tip of catheter reached DGCV in 39.84% VAs (49/123), reached target sites in 35.87% VAs (44/123), and achieved successful ablation in 30.89% VAs (38/123), which was significantly lower than by SS approach (88.61% (70/79), 84.81 % (67/79), and 75.95% (60/79), P<0.05). There were no significant differences in complication occurrence between NS approach and SS approach (4/123, 3.25% vs 7/79, 8.86%, p>0.05). Angle between DGCV and AIV<83° indicated an inaccessible AIV by catheter tip with a predictive value of 94.5%. Width/height of coronary venous system>0.69 more favored a SS approach with a predictive value of 87%. CONCLUSION For radiofrequency catheter ablation (RFCA) of VAs arising from DGCV-AIV, the SS approach facilitates the catheter tip achieve target sites and contributes to a successful ablation.